Agreeing with the meanings of the selected wordsIn the poems of Layla Al Amriya (Damascus University Journal of arts and humanities sciences, 2024)
This is an existing study about the word and the meaning in general, and about the agreement between the word and the meaning in the poems of Layla Al -Amiriya in particular, for the goal that the study is based is the disclosure of this arrest in its poems through the fact that it is a matter.The study necessitated a prelude to it by talking about the two issues of wording and meaning among the ancient scholars and critics among them.And the hadith scholars, as I began the study by mentioning Layla and her lineage and what had occurred of disagreement therein, and she mentioned some of her news with Qais bin AlmolawehAnd what was between them of love and affection, as I mentioned what reached us of her poems, and I mentioned in my study of her poems.Some of the stories that prompted her to tell the verse or verses, and I ended this study by confirming this concordance, and concluded it with an appropriate conclusion appended to the most prominent results that I concluded and a list of my references and references.
Keywords: The word; the meaning; the harmony.